Communicative language teaching: High school teachers' attitudes and classroom practices in the context of An Giang : - Lý, Thị Thanh Trúc (Can Tho University, 2008)
This study is an attempt to investigate the An Giang high school FEL teachers' attitudes towards CLT and the extent to which the teachers materialize their attitudes in classroom practice.